Denudatine-type diterpenoid alkaloids from an aqueous extract of the lateral root of Aconitum carmichaelii. Issue 7 (28th June 2021) - Liu, Hui; Shao, Shuai; Xia, Huan; Wu, Yu-Zhuo; Zhu, Cheng-Gen; Xu, Cheng-Bo; Zhang, Tian-Tai; Guo, Qing-Lan; Shi, Jian-Gong
Abstract: Five new denudatine-type diterpenoid alkaloids (1–5), along with the known analogue aconicarmine (6 ), were isolated from an aqueous decoction of the lateral roots of Aconitum carmichaelii (fu-zi). Their structures were determined by spectroscopic data analysis and electronic circular dichroism (ECD) calculations. Compound 5 is the first denudatine-type diterpenoid alcohol iminium alkaloid, which could be partially transformed into the aza acetal form in pyridine- d 5 . Compound 5 inhibited mice writhing in an acetic acid-induced writhing assay. Graphical Abstract: UF0001